Cross-Cultural Counselling and Cross-Cultural Meanings: An Exploration of Morita Psychotherapy - Aldous, Jane L. (Canadian Journal of Counselling and Psychotherapy, 2007)
This paper outlines the theoretical framework and techniques of an Eastern approach to psychological change called Morita psychotherapy. It demonstrates that the meanings of terms which describe counselling styles can differ from culture to culture and particularly from East to West. It is argued that such differences have implications for cross-cultural counselling. Western research indicates that Asian ,Vmerican clients prefer approaches that are more "activedirective," "logical," "rational," and "structured." It is suggested that despite efforts to the contrary, an ethnocentric approach to counselling may inadvertently be imposed upon clients of Asian origin via the interpretation and application of such terms.